Determinants of capital structure in the hospitality industry: Impact of clustering and seasonality on debt and liquidity. (April 2022) - Sikveland, Marius; Xie, Jinghua; Zhang, Dengjun
Abstract: Volatile seasonal demand and geographic clustering of firms are two important factors affecting the capital structure of hospitality firms. In this paper, we investigate the capital structure determinants of hospitality firms regarding the effects of seasonality and geographic clustering. A fixed-effects panel data model was estimated using data on all hospitality firms in Norway from 2008 to 2018. Our empirical findings reveal that the seasonality created by foreign tourists increases the share of long-term debt in the capital structure. Further, the clustering of hospitality firms in a region enhances firm reliance on short-term debt, in that firm liquidity is negatively associated with the degree of clustering, suggesting that severe competition drains cash for which short-term debt serves as a substitute. These findings have important implications for financial management of firms in the hospitality industry as the degrees of seasonality and clustering significantly affect their asset financing and liquidity management behavior. Highlights: Firm-level capital structure in the hospitality industry is investigated. The impact of seasonality and firm clustering is measured. Seasonality increases long-term debt dependence in the industry. Firm clustering results in less liquidity among firms. The impact of our results on financial management is discussed.